Therapeutic drug monitoring of anti-TNF biologics in patients with Crohn's disease at Groote Schuur Hospital, Cape Town, South Africa - Sungay, Mohamed Yaaseen (Department of Medicine, 2025)
Monoclonal antibodies targeting Tumour Necrosis Factor-α (TNF α) have revolutionised the management of Inflammatory Bowel Disease (IBD) and have proved highly effective in both inducing and maintaining remission in both ulcerative colitis (UC) and Crohn's disease (CD). The advent of Therapeutic Drug monitoring (TDM) in recent years has allowed further optimisation of their use. TDM involves the measurement of serum trough levels (TLs) and anti-drug antibodies (ADAs), with higher serum drug concentrations and the absence of ADAs associated with favourable therapeutic outcomes. Adjustment of anti-TNF therapy based on reactive TDM in patients who are either primary non-responders or have secondary loss of response to these biologics is associated with superior clinical outcomes when compared to empiric escalation of therapy. In this study we explore the efficacy of TDM since it was first implemented in our practice and the impact on clinical outcomes in patients with CD in our resource limited setting. Method A retrospective cohort study was performed on all patients with CD treated with an anti-TNF biologic, either infliximab or adalimumab, who underwent TDM since it was first implemented in the IBD clinic at Groote Schuur hospital, Cape Town, South Africa in between July 2018, and March 2023. Hospital records were analysed, and relevant demographic variables and clinical outcomes were extracted. Results Sixty-nine patients with Crohn's Disease started treatment with an Anti TNF, of which 53 were identified to have had undergone reactive TDM. Forty seven (90%) were treated with an immunomodulator prior to starting anti TNF therapy. The median time from initiation of anti TNFs to first TDM was 9.5 months (IQR5-35); 35 patients (67%) had sub-therapeutic trough levels at that time. No significant predictors of sub-therapeutic trough levels were identified, notably there was no association with disease activity, behaviour, location, or the presence of perianal disease. Adjustment of anti-TNF therapy based on reactive TDM was only performed in 24 patients (45.3%); in all other patients there was no adjustment to the anti TNF therapy. Escalation of biologic therapy based on TDM results in patients with sub- therapeutic TL and no ADAs did not impact clinical remission or response rates at 3 or 6 months of follow up. Conclusion In our cohort most patients that underwent TDM had sub-therapeutic trough levels; no significant predictors of sub-therapeutic trough levels were identified. Neither dose optimisation or switching to a 2nd anti-TNF proved effective in achieving clinical remission at either 3 or 6 months of follow up.